Expressive Speech Acts Analysis of â€œSonic the Hedgehog 2â€ Movie - Joseph Anderson Gulo; Arsen Nahum Pasaribu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to find expressive speech acts and the meaning presented based on its categories is in accordance with the actual context in Sonic The Hedgehog 2 movie script. This research was designed using descriptive qualitative method. In this research, the researcher used himself (human instrument) as a research instrument, because of the position of the researcher as a planner, implementer of data collection, implementer of data analysis, interpretation, and becomes a reporter for the findings. By using Searleâ€™s theory (illocutionary act), the research results showed that of 963 utterances uttered by all actors in the Sonic The Hedgehog 2 movie, the researcher took 10 samples representing all utterances that included in the expressive speech acts with data divided into 7 types of speech acts according to Searle (illocutionary act) in Leech (1983), with the distribution of data as follows: reproach consists of 2 data (20%); liking of 1 data (10%); disliking of 2 data (20%); blaming of 1 data (10%); greeting of 2 data (20%); congratulating of 1 data (10%); and welcoming as many as 1 data (10%).